Experience in the Management of Patients with Chronic Vascular Ulcers of the Lower Limbs Using Negatively Charged Polystyrene Microspheres - María Teresa Cacua Sánchez (International Journal of Vascular Medicine)
Background. Chronic ulcers of the lower limbs are a socioeconomic health problem, having a high incidence in the adult population. Despite a correct etiological treatment, in addition to the multiple lesion management options available, healing percentage and speed remain low, which makes it a great therapeutic challenge. Objective. To describe the outcome and effectiveness of the use of PolyHeal® Micro in the granulation and epithelialization of chronic ulcers of the lower limbs. Methods. Descriptive observational case series of 19 patients with diagnosis of chronic vascular ulcers of the lower limbs, treated at Medical Center Nuestra IPS and Medical Center Juan Pablo II in Bogotá between March 2018 and December 2018, who received PolyHeal® Micro as topical treatment for their lesions. Patients were assessed taking into account age, sex, ulcer size, pain, wound exudate, as well as granulation and epithelialization response. Results. In this series, the mean age of patients was 67.9 years, they were mostly females (84%), and the most common location of ulcers was the internal malleolus (50%). In terms of wound severity, 47% were found to be severe, 43% moderate, and 10% mild. The median time of lesion onset was 28 weeks, with a maximum of 2080 and a minimum of 8 weeks. In total, 87% of the ulcers were of venous etiology. After 12 weeks of treatment with Polyheal, ulcers showed a significative improvement of Wollina score means: 0.80 ± 0.90–5.90 ± 1.47; p<0.000. Wound area mean at the start of treatment was 31.6 cm2, and at the end of treatment was 17.85 cm2, which is equivalent to a wound area surface reduction of 54.2%, with a statistically significant p value. The interquartile range showed a reduction of 64.3% in the central means of wounds. Seventy percent of the patients reached a granulation percentage greater than 70%, 17% of the lesions exhibited an improvement of 30–70%, and there was an overall granulation improvement in 87% of the patients. Concerning epithelialization, 40% of patients reached a percentage higher than 70%, and 17% of patients between 30% and 70%. Treatment time was 12 weeks in 68% of cases, with an average response time of 8.1 weeks. Based on the visual analogue scale (VAS), a reduction in patients’ perception of pain was achieved, dropping from an average of 6 (moderate to severe pain) to 2 (little pain), demonstrating an improvement in this regard. Fifty percent of the ulcers showed decreased exudate, resulting in a dry state. The patient satisfaction rate at the end of treatment was 89%. Conclusion. The use of PolyHeal® Micro for an average of 8.1 weeks of treatment showed a high rate of granulation and epithelialization in chronic ulcers of the lower limbs, improving pain perception in these patients and generating a high degree of treatment satisfaction.